PERILAKU POLINATOR Elaeidobius kamerunicus Faust (COLEOPTERA : CURCULIONOIDAE) PADA PEMBUNGAAAN KELAPA SAWIT (Elaeis guineensis Jacq) - Dwi Afrian; Wiwin Windriyanti; Sri Wiyatiningsih (UPN VETERAN JAWA TIMUR, 2020)
Oil palm (Elaeis quineensis Jacq) is a monocious plant whose pollination process requires pollinating agents such as insects (entomofily). E. kamerunicus insects is a palm oil specific pollinator insect. The existence of E. kamerunicus can be the value of Fruit set of oil palm bunches. This research aimed to study the behavior of E. kamerunicus pollinators on the flowering of oil palms, so that the information obtained was useful to evaluate the effectiveness of E. kamerunicus as pollinators. The purposive sampling method used to determine the sample plant, while observed the behavior of visit used the focal sampling method. Based on observation of the E. kamerunicus behavior, it was found that the duration of E. kamerunicus visited 17.87 seconds / flower, with the length of flowering activity on the first, second and third days each 3.29 minutes, 1.39 minutes and 0.57 minutes, then the visited rate of E. kamerunicus was based on female flowers and male flowers, it was 2.32 flowers / minute and 3.18 flowers / minute, while the visited rate of E. kamerunicus was based on male E. kamerunicus and female E. kamerunicus on male flowers 3.53 flowers / minute and 2.84 flowers / minute with a period of time to visited E. kamerunicus on female flowers at 09.00-13.00 WIB and the average number of individuals E. kamerunicus male and female on female oil palm flowers respectively 5 tails and 15 tails.